Método Pilates en la prevención de caídas del adulto mayor. - Materano Cordovilla, Carlos Fidel (2025)
Background. Falls are one of the leading causes of death in older adults, increasing healthcare costs and affecting their independence. In response to this, the Pilates method has emerged as an exercise program adapted to improve their physical condition and prevent these risks. Objective. The objective of this research was to determine the effects of the Pilates method as a technique for preventing falls in older adults, based on a literature review that examines scientific evidence supporting its dosage and clinical application. Methodology. The research corresponds to a documentary-type literature review carried out by searching for information in various databases. The methodology included critical assessment from an educational perspective, incorporating the analysis and synthesis of evidence to inform both clinicians and educators. The selection of sources was evaluated using the Physiotherapy Evidence Database and Scimago Journal & Country Rank tools. Finally, 22 articles met the necessary criteria and were included in the research. Results. The results showed that the Pilates Method improves balance, coordination, strength, and functional independence, while also reducing falls and increasing quality of life in older adults. Conclusion. In conclusion, Pilates is presented as a safe, beneficial, and viable alternative for fall prevention in this population, strengthening physical abilities essential for their autonomy. Its implementation in regular exercise routines by health professionals and caregivers could significantly contribute to reducing the incidence of falls and enhancing the quality of life for older adults.